The effect of COVID-19 on student opportunities to acquire airway skills. (2nd October 2022) - Barr, Nigel; Donathan, Erin; Ockey, Ryan
Abstract : Background: To protect healthcare providers during the COVID-19 pandemic, substantial changes were made to clinical care guidelines across the United States. Alongside these changes, emergency medical services call volume decreased nationwide. These made it difficult for paramedic students to practise and master the practical skills necessary for skill competency and graduation. The aim of this study was to explore the changes in the number of opportunities available to paramedic students during the COVID-19 pandemic. Methods: A retrospective study of student records was carried out to explore airway procedure variables before and after the beginning of the COVID-19 pandemic. Results: Statistically significant differences in case exposure were found between the periods before and after the start of the COVID-19 pandemic. Case volume and opportunities to practise most airway procedures decreased post COVID-19. However, procedures associated with higher-acuity patients, such as intubation, increase in frequency. Conclusion: The pandemic gave rise to difficulties for paramedic educators in preparing students for qualification and the current study has highlighted such unique challenges. Consideration must be given to developing a more flexible, adaptable and scalable way to measure a student's competency in paramedicine in times of significant disruption.